On the equation for the vertical velocity of atmospheric air - Kantsyrev Boris (EPJ Web of Conferences)
The conditions for the inertialess approximation of the equation for the vertical velocity of humid atmospheric air are considered, under which the inertia of the vertical and horizontal motion can be considered small. The resulting equation can be used in calculations of atmospheric processes.